2019
DOI: 10.1111/jzs.12331
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudoplagioporinae, a new subfamily in the Opecoelidae Ozaki, 1925 (Trematoda) for a small clade parasitizing mainly lethrinid fishes, with three new species

Abstract: The Pseudoplagioporinae n. subf. (Opecoelidae) is proposed for species of Pseudoplagioporus Yamaguti, 1938, Fairfaxia Cribb, 1989, and Shimazuia Cribb, 2005, a small group of relatively distinctive, Indo‐West Pacific taxa reliably known almost entirely from emperor fishes (Perciformes: Lethrinidae). These taxa were previously recognized in the Plagioporinae Manter, 1947, but that subfamily has recently been restricted to a clade of Holarctic, freshwater taxa, whereas analyses of new genetic data find the pseud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 69 publications
(145 reference statements)
1
11
0
Order By: Relevance
“…To assess the phylogenetic affinities of nominal stenakrine taxa, maximum likelihood and Bayesian inference analyses were performed against a concatenated 18S + 28S alignment including the novel data as well as other relevant sequences from GenBank. Sequences for general alignment of the main subfamilies/clades, including the Opecoelidae, other xiphidiate families belonging to the Gorgoderoidea, Haploporoidea, Troglotrematoidea, Microphalloidea, Plagiorchioidea and Brachycladioidea, as well as non-xiphidiate taxa including from the Monorchiata, Lepocreadiata, Opisthorchiata, Apocreadiata, Gymnophallata, and Hemiurata were downloaded from GenBank database [3,8,9,11,18,20,22,27,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] with custom R script [45] based on the "ape" package [46]. To concatenate sequences of 18S and 28S rRNA genes "catfasta2phyml.pl" script [47] was used with "-f" parameter.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…To assess the phylogenetic affinities of nominal stenakrine taxa, maximum likelihood and Bayesian inference analyses were performed against a concatenated 18S + 28S alignment including the novel data as well as other relevant sequences from GenBank. Sequences for general alignment of the main subfamilies/clades, including the Opecoelidae, other xiphidiate families belonging to the Gorgoderoidea, Haploporoidea, Troglotrematoidea, Microphalloidea, Plagiorchioidea and Brachycladioidea, as well as non-xiphidiate taxa including from the Monorchiata, Lepocreadiata, Opisthorchiata, Apocreadiata, Gymnophallata, and Hemiurata were downloaded from GenBank database [3,8,9,11,18,20,22,27,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] with custom R script [45] based on the "ape" package [46]. To concatenate sequences of 18S and 28S rRNA genes "catfasta2phyml.pl" script [47] was used with "-f" parameter.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…For example, the absence of the canalicular seminal receptacle is also typical for opecoelines, and Shimazuia Cribb, 2005 (Pseudoplagioporinae) is defined for relatively short fields of vitelline follicles [7]. However, all together they do not occur in any subtaxon of the Opecoelidae (compare with [3,4,7,9,11]). The Stenakridae stat.…”
Section: Taxonomymentioning
confidence: 99%
See 2 more Smart Citations
“…Cryptogonimids in lutjanids and pseudoplagioporine opecoelids in lethrinids are two groups which have been relatively thoroughly surveyed, yet Miller & Cribb (2013) found Siphomutabilus bitesticulatus Cribb, 2013 andS. raritas Miller &Cribb, 2013 in only 1 of 21 Pterocaesio marri (Schultz) and 1 of 18 Caesio cuning (Bloch) respectively, and Martin et al (2020a) found Pseudoplagioporus lethrini Yamaguti, 1938 in only 1 of 51 Lethrinus miniatus (Forster) and 1 of 60 Lethrinus nebulosus (Forsskål). The nature of sampling is such that rarity is ultimately only demonstratable at local scales, and it remains possible that R. pansho is more common elsewhere, and/or in habitats, fishes or at depths beyond those we have surveyed.…”
Section: Discussionmentioning
confidence: 99%